National development in the Third World - Ágh, Attila (Budapest : Institute for World Economy of the Hungarian Academy of Sciences, 1984)
This book examines the national development of the third world countries.
Bibliography: p. 59-68.
oo 23/01/2019
Loans
Keywords: Nationalism and socialism